Translational and rotational diffusion of a single nanorod in unentangled polymer melts - Kim, Min Jung; Cho, Hyun Woo; Kim, Jeongmin; Kim, Heesuk; Sung, Bong June (AMER PHYSICAL SOC, 2015)
Polymer nanocomposites have been an issue of both academic and industrial interest due to promising electrical, mechanical, optical, and magnetic properties. The dynamics of nanoparticles in polymer nanocomposites is a key to understanding those properties of polymer nanocomposites and is important for applications such as self-healing nanocomposites. In this article we investigate the translational and the rotational dynamics of a single nanorod in unentangled polymer melts by employing extensive molecular dynamics simulations. A nanorod and polymers are modeled as semiflexible tangent chains of spherical beads. The stiffness of a nanorod is tuned by changing the bending potential between chemical bonds. When polymers are sufficiently long and the nanorod is stiff, the nanorod translates in an anisotropic fashion along the nanorod axis within time scales of translational relaxation times even in unentangled polymer melts. The rotational diffusion is suppressed more significantly than the translational diffusion as the polymer chain length is increased, thus the translational and rotational diffusion of the nanorod are decoupled. We also estimate the winding numbers of polymers, i.e., how many times a polymer winds the nanorod. The winding number increases with longer polymers but is relatively insensitive to the nanorod stiffness.
Keywords: MOLECULAR-DYNAMICS; NANOPARTICLE DIFFUSION; NANOCOMPOSITES; MODEL; COMPOSITES; STRATEGIES; DISPERSION; ORIGINS; LENGTH